Intranasal inoculation of sows with highly pathogenic porcine reproductive and respiratory syndrome virus at mid-gestation causes transplacental infection of fetuses. (December 2015) - Wang, Tongtong; Wang, Xiaofei; Li, Xin-an; Nie, Li; Zhang, Minxia; Liu, Sidang; Zhao, Xiaomin; Shang, Yingli; Zhou, En-min; Hiscox, Julian; Xiao, Yihong
Abstract Transplacental infection plays a critical role in the reproductive failure induced by porcine reproductive and respiratory syndrome virus (PRRSV), yet exposure of sows and gilts to classical PRRSV generally leads to reproductive failure after 85 days of gestation. We report, for the first time, that the susceptibility of fetuses to highly pathogenic PRRSV (HP-PRRSV) is similar at 60 days and 90 days of gestation. This difference from classical PRRSV may contribute to its high pathogenicity. A field study of the HP-PRRSV vaccine in pregnant sows at mid-gestation should be considered.